1998
DOI: 10.1176/ps.49.5.678
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Victimization on Clinical Outcomes of Homeless Persons With Serious Mental Illness

Abstract: These findings suggest the critical need for service providers who work with homeless people with serious mental illness to assess the extent to which they have been victims of crime and to address issues of victimization and safety along with psychiatric and social adjustment problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
91
0
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(103 citation statements)
references
References 6 publications
5
91
0
4
Order By: Relevance
“…The results are consistent with many other studies on QoL of mentally ill. The studies showed significant differences in quality of life of clinical and non-clinical groups (Murphy, H. and Murphy, E.K., 2006), greater QOL variability in patients with low function scores compared to those with medium and high function scores (Becker, T., et al ,2005), quality of life was associated with decreased psychotic and depressive symptoms, reduced substance abuse, fewer days of homelessness, and increased social support, income, employment, and service use ( Lam, J.A. and Rosenheck, R. ,2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results are consistent with many other studies on QoL of mentally ill. The studies showed significant differences in quality of life of clinical and non-clinical groups (Murphy, H. and Murphy, E.K., 2006), greater QOL variability in patients with low function scores compared to those with medium and high function scores (Becker, T., et al ,2005), quality of life was associated with decreased psychotic and depressive symptoms, reduced substance abuse, fewer days of homelessness, and increased social support, income, employment, and service use ( Lam, J.A. and Rosenheck, R. ,2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the experience of criminal victimization exerts a small prospective influence on worse quality of life outcomes among persons with severe mental illness. Specifically, in a multisite sample of over nearly 2000 homeless persons with severe mental illness, Lam and Rosenheck (1998) found that more self-reported criminal victimization experiences at baseline were associated with poorer life satisfaction at 3-and 12-month follow-ups.…”
Section: Transitory/episodic Experiences and Functioning/well-beingmentioning
confidence: 99%
“…The rationale for this is that residence in impoverished areas with higher rates of crime places individuals at greater risk of being criminally victimized. There is evidence for this hypothesis from cross-sectional studies indicating that residence in poor urban areas is associated with higher rates of criminal victimization among people with mental illness (Hiday, Swartz, Swanson, Borum, & Wagner, 1999;Lam & Rosenheck, 1998). Prospective studies are lacking in this area.…”
Section: Enduring Environmental Conditions and Transitory/episodic Exmentioning
confidence: 99%
“…Shinn et al (1998) and Weitzman et al (1990) found higher earlier exposure to violence among families that entered homeless shelters relative to those that remained housed, but Lehmann et al (2007) and Shelton et al (2009) In the U.S., 0.9 percent of people 12 and over reported being physically assaulted in 2014 (Truman & Langton, 2015). While everyone faces some risk of victimisation, people of lower socioeconomic status (Hotaling & Sugarman, 1990) and homeless people face much higher risks (Burt et al, 2001;Fischer, 1992;Garland et al, 2010;Geissler et al, 1995;Kipke et al, 1997;Lam & Rosenheck, 1998;Lee & Shreck, 2005;Wenzel et al, 2001). …”
Section: Previous Studiesmentioning
confidence: 99%
“…A large research literature documents how domestic violence is associated with women's and children's subsequent homelessness (see, e.g., Bassuk et al, 2001; Flinders Institute for Housing, Urban and Regional Research, 2008;Weitzman et al, 1990). Studies also show that homeless men and women suffer higher rates of victimisation than their housed counterparts (Burt et al, 2001;Jasinski et al, 2005;Lam & Rosenheck, 1998;Lee & Schreck, 2005;Wenzel et al, 2001). However, less is known about how violence might trigger men's housing problems.…”
mentioning
confidence: 99%